2023
DOI: 10.1186/s13578-023-00967-y
|View full text |Cite
|
Sign up to set email alerts
|

Ang-(1–7)/MasR axis promotes functional recovery after spinal cord injury by regulating microglia/macrophage polarization

Abstract: Background Inflammatory response is an essential part of secondary injury after spinal cord injury (SCI). During this period, the injury may be exacerbated through the release of a large number of inflammatory factors and the polarization of infiltrating macrophages and microglia towards M1. Ang-(1–7), mainly generated by Ang II via angiotensin-converting enzyme 2 (ACE2), can specifically bind to the G protein-coupled receptor Mas (MasR) and plays an important role in regulating inflammation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In the current study, it was found that p-p65/p65 was decreased by BMSC-Exo-derived miR-216a-5p, which indicated that BMSC-Exo-derived miR-216a-5p inactivated the NF-κB pathway. In terms of the detection of TLR4/β-ACTIN and myD88/β-ACTIN, we used β-ACTIN as the internal reference to reflect the expression of TLR4 and myD88 proteins, which was in line with previous studies ( Liu et al, 2020 ; Rong et al, 2021 ; Gu et al, 2023 ). Overall, this study discovered that BMSC-Exo-derived miR-216a-5p reduced the TLR4/β-ACTIN, myD88/β-ACTIN, and p-p65/p65 in SCI rats, which indicated that BMSC-Exo-derived miR-216a-5p inactivated the TLR4/NF-κB pathway in SCI rats.…”
Section: Discussionmentioning
confidence: 95%
“…In the current study, it was found that p-p65/p65 was decreased by BMSC-Exo-derived miR-216a-5p, which indicated that BMSC-Exo-derived miR-216a-5p inactivated the NF-κB pathway. In terms of the detection of TLR4/β-ACTIN and myD88/β-ACTIN, we used β-ACTIN as the internal reference to reflect the expression of TLR4 and myD88 proteins, which was in line with previous studies ( Liu et al, 2020 ; Rong et al, 2021 ; Gu et al, 2023 ). Overall, this study discovered that BMSC-Exo-derived miR-216a-5p reduced the TLR4/β-ACTIN, myD88/β-ACTIN, and p-p65/p65 in SCI rats, which indicated that BMSC-Exo-derived miR-216a-5p inactivated the TLR4/NF-κB pathway in SCI rats.…”
Section: Discussionmentioning
confidence: 95%
“…These results suggest that Ang-(1-7) can regulate microglia polarization toward the M2 type in vivo, which is consistent with the results of the in vitro experiment. In addition, MasR expression was also upregulated in the TS group, suggesting that the upregulation of MasR may be related to the macrophage activation status rather than to a specific phenotype [13]. Interestingly, HE staining revealed a more pronounced demarcation between the damaged area and the surrounding normal tissue in the TS+Ang-(1-7) group than in the TS group.…”
Section: Plos Onementioning
confidence: 89%
“…Recent studies have shown that the Ang-(1-7)/MasR axis is a protective arm of the renin-angiotensin system against inflammation and improves the prognosis of TBI [11,12]. Guangjin Gu et al suggested that Ang-(1-7) could regulate microglia polarization from M1 to M2 phenotype after spinal cord injury, thereby promoting functional recovery [13].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, both ACE2 and MasR are primarily expressed on macrophages and are markedly reduced upon LPS stimulation in vitro . Activation of the Ang-(1–7)-MasR cascade can shift macrophages toward the M2 phenotype by inhibiting MAPK and TLR4-IKK–NF–κB signals in sepsis [ 34 , 56 ]. Moreover, administration of an ACE2 activator reduces the inflammatory effect in retinal pigment epithelium cells by blocking the MAPK–NF–κB pathway following LPS stimulation [ 57 ].…”
Section: Discussionmentioning
confidence: 99%